Keamanan dari Represi dan Penyelesaian Tindak Pidana Berat HAM: Studi Komparatif Argentina, Kamboja dan Yunani - Amaritasari, Indah (Jurnal Keamanan Nasional, 2024)
Human rights are often perceived as obstacles to achieving national security, especially in the context of addressing past serious human rights violations. State repression plays a role in national security by impacting national stability, public trust, radicalization risks, international reputation, and economic outcomes. Thus, it is essential to examine how different countries have approached the resolution of past serious human rights crimes and how these approaches contribute to security from the perspective of repression management. Argentina, Cambodia, and Greece represent regions that have endured past severe human rights violations. The processes of addressing these violations in these countries offer valuable insights that Indonesia can consider in addressing its historical human rights issues. This study finds that nations like Greece and Argentina, which have effectively resolved past human rights abuses and gained international support, have seen reductions in repression, thus enhancing the intended security outcomes. In contrast, Cambodia's delayed and fragmented approach, lacking state commitment and international attention, has resulted in differing impacts on security compared to the outcomes observed in Greece and Argentina.